Exploring Factors Influencing Gen Z's Acceptance and Adoption of AI and Cloud-Based Applications and Tools in Academic Attainment - Ghilan Al-Madhagy Taufiq Hail; Shafiz Affendi Mohd Yusof; Ammar Rashid; Ibrahim El-Shekeil; Abdalwali Lutfi (Ital Publication, 2024)
Generation Z faces diverse challenges in education amidst the swift evolution of technology. This study investigates the factors shaping Generation Z's acceptance and adoption of AI and Cloud-based applications in Oman's higher education sector. Despite limited attention to this area in Oman and the Gulf Cooperative Council countries (GCC), this research addresses the gap by employing the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, recognized for its effectiveness in understanding technology adoption. Through a quantitative approach, Generation Z students in Omani higher education institutions were surveyed, and SmartPLS was utilized for analysis. Results indicate a significant positive relationship between all UTAUT antecedent factors, with Performance Expectancy being non-significant. This study offers novel insights into global understandings of Generation Z's learning trends with AI and Cloud-based applications in higher education, aiming to enhance pedagogical approaches. Notably, it pioneers such efforts within the GCC context. Recommendations for similar research in other GCC countries are provided to enrich regional perspectives. Limitations and future directions are addressed, emphasizing the importance of comprehending Generation Z's interaction with technology to advance educational practices in the digital age. Doi: 10.28991/ESJ-2024-08-03-02 Full Text: PDF